Profiling of phospholipid molecular species in human breast milk of Chinese mothers and comprehensive analysis of phospholipidomic characteristics at different lactation stages. (30th June 2021) - Song, Shuang; Liu, Ting-Ting; Liang, Xue; Liu, Zhao-Yan; Yishake, Dinuerguli; Lu, Xiao-Ting; Yang, Meng-Tao; Man, Qing-Qing; Zhang, Jian; Zhu, Hui-Lian
Highlight: Precise qualitative and quantitative analysis of phospholipid molecular species. 258 phospholipid molecular species were characterized in 486 human milk samples. Dynamic changes of classes and sub classes of phospholipid over time were analyzed. Critical change of phospholipid profile between lactation periods were analyzed. Abstract: Phospholipids are critical for milk digestion and infant development. But the profile of phospholipid molecular species in human milk and its dynamic changes during the lactation period have never been reported. The present study elucidated precise qualitative and quantitative analysis of 258 phospholipid molecular species in 486 human milk samples. Phosphatidylcholine is the most abundant class, followed by phosphatidylserine, phosphatidylethanolamine and sphingomyelin as the second abundant class in different lactation period. The plasmalogens declined along the lactation period, and the polyunsaturated-phospholipids decreased after 10–15 days. The decrease of phosphatidylcholines and phosphatidylglycerols, and the increase of lysophosphatidylethanolamines and lysophosphatidylcholines are critical changes from 0 to 5 days to 10–15 days; increase of phosphatidylinositols, phosphatidylserines, lysophosphatidylethanolamines and lysophosphatidylcholines is the key changes from 10–15 days to 40–45 days; the decrease of most phospholipid molecular species is the characteristic change from 40–45 days to 200–240 days; and the phospholipid profile achieved stability after 200 days.